O projeto crítico de Samuel Johnson no The Rambler: uma crítica literária entre os antigos e os modernos - Castro, Diego de (Universidade Federal de São Carlos, 2024)
The aim of this thesis is to conduct a political reading of Samuel Johnson's literary criticism in his series of essays titled The Rambler (1750-52), initially published as a periodical. This analysis will demonstrate that the argumentative structure of Johnson’s literary criticism, in addressing the aesthetic debates of his era - particularly the quarrel between the ancients and the moderns - constitutes a critical project that, in its form, dramatizes the bourgeois intellectual’s attempt to reclaim an idealized sphere of early 18th-century England. This ideal space was represented by a bourgeois public sphere, a symbol of a historical moment characterized by an intimate connection between the literary critic and his reading public, a context increasingly eroded by the advancing productive forces of a new phase of capitalism and the dissolution of the Ancien Régime. As the central object of this study is Johnson’s literary criticism, this analysis will center on essays from Rambler numbers 1, 3, 4, 36, 37, and 156.
Samuel Johnson's critical project in The Rambler: a literary critiscism between the ancients and the moderns
Keywords: Samuel Johnson; The Rambler; Leitura política; Ensaio; Crítica literária; Political reading; Essay; Literary criticism; LINGUISTICA, LETRAS E ARTES::LETRAS::LINGUAS ESTRANGEIRAS MODERNAS; LINGUISTICA, LETRAS E ARTES::LETRAS::TEORIA LITERARIA